5x+2=2x-10 x=-4
5x - 10 = 3x + 2 5x - 3x = 2 + 10 2x = 12 x = 12/2 x = 6
10x2 + 21x - 10 = 10x2 + 25x - 4x - 10 = 5x(2x + 5) - 2(2x + 5) = (2x + 5)(5x -2)
2x +1 = 5x-2 2x +3= 5x 3 = 3x x=1
x+2x+14=5x+214-2=5x+2x+x10=8x10/8=xx=5/4 ans.
5x+2=2x-10 x=-4
If you mean: (2x+2)(5x-5) then it is equivalent to 10x^2 -10
If that was 2x^2 + 5x + 2, it would factor to (2x + 1)(x + 2)
5x - 10 = 3x + 2 5x - 3x = 2 + 10 2x = 12 x = 12/2 x = 6
10x2 + 21x - 10 = 10x2 + 25x - 4x - 10 = 5x(2x + 5) - 2(2x + 5) = (2x + 5)(5x -2)
3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3
2x +1 = 5x-2 2x +3= 5x 3 = 3x x=1
x+2x+14=5x+214-2=5x+2x+x10=8x10/8=xx=5/4 ans.
-3x+2 = 2x-8 8+2 = 2x+3x 10 = 5x x = 2
x=6Solution:x + 2x + 14 = 5x + 214 - 2 = 5x - 3x12 = 2xx = 12/2 = 6
8x-7 plus 2x equals 6 plus 5x plus 2?
3x - 8 = 5x + 2 <+8 and - 5x off each side> -2x = 10 <divide each side by -2x> x = -5